2009
DOI: 10.1007/s11099-009-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

Blue radiation stimulates photosynthetic induction in Fagus sylvatica L.

Abstract: This study was designed to test the hypothesis that the spectral composition of incident radiation, as defined by the relative proportions of blue (B; λ max = 455 nm) and red (R; λ max = 625 nm) photons, can affect photosynthetic induction, since B photons stimulate stomatal opening and are more effectively absorbed by leaves than R photons. Different stages of photosynthetic induction, primarily determined by the photo-modulation of Rubisco activity and stomata opening, were investigated in dark-adapted leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…This suggests that the overall effect of light conditions on photosynthesis might be mediated through a stomatal response rather than any direct effect on light on the photosynthetic machinery. This is an important conclusion as others (Portis et al 2008) have suggested that blue light can activate Rubisco and enhance electron transport in the thylakoid membranes (Košvancová-Zitová et al 2009b). …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This suggests that the overall effect of light conditions on photosynthesis might be mediated through a stomatal response rather than any direct effect on light on the photosynthetic machinery. This is an important conclusion as others (Portis et al 2008) have suggested that blue light can activate Rubisco and enhance electron transport in the thylakoid membranes (Košvancová-Zitová et al 2009b). …”
Section: Discussionsupporting
confidence: 53%
“…An additional hypothesis relates to the blue light component of the in-canopy light climate. Stomata are known to be especially responsive to light between 430 and 470 nm (Raschke 1975;Morison and Jarvis 1983;Karlsson 1986;Briggs and Christie 2002), and there are also reports of a direct blue light effect on the induction kinetics of photosynthesis (Košvancová-Zitová et al 2009b), and on the electron transport through thylakoid membranes (Portis et al 2008;Košvancová et al 2009a). Blue light enrichment inside coniferous canopies has been observed under cloudy skies (Urban et al 2007), and so it is not unreasonable to suppose that part of the enhancement of photosynthesis under cloudy and overcast Communicated by Nina Buchmann. conditions is caused by blue light enrichment.…”
Section: Introductionmentioning
confidence: 99%
“… Although there are reports of a stimulating effect of blue light on the hydraulic conductance of leaf blades (Sellin et al. 2011) and on the activation of photosynthetic processes (Kosvancova‐Zitova et al. 2009), blue light enrichment in diffuse conditions did not cause a substantial stimulation of photosynthesis through its effect on stomatal conductance (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Blue light often stimulates stomatal opening when combined with red light (Zeiger and Field 1982, Wang et al 2008, Zait et al 2017, and adding blue to dynamically changing red light intensities may ameliorate stomatal limitation on carbon gain. To date, however, only few studies have explored blue light effects on photosynthetic induction (Košvancová-Zitová et al 2009, Zhang et al 2011, Kaiser et al 2017, and available findings are contradictory. Interestingly, the stimulating effect of blue light on stomatal opening seems to be highly sensitive to the growth environment.…”
Section: Introductionmentioning
confidence: 99%